Carbon-based nanocomposites for energy storage - Ee, Shu Jing (2017)
As portable consumer electronics become the necessities in one’s daily life, energy storage systems which act as the primary power sources are attracting rising attention in their development. One of the great challenges is to develop ecologically friendly, low cost and sustainable energy storage system. The performance of these storage systems, for example, supercapacitors and lithium ion batteries, is strongly reliant on their materials of choice for electrode. Hence, much interest has been garnered in looking for innovative and advanced material that can overcome current technology hurdles. In this dissertation, various carbon based nanocomposites have been explored to enhance the performance of the energy storage device by synergistic integration of the conductive carbon nanomaterials and reactive nanomaterials. Novel carbon-based nanostructured-composites that can be utilized as the electrode material for constructing lithium ion batteries and supercapacitor has been synthesized. If suitable, carbon based nanocomposites has been demonstrated to fabricate flexible energy storage systems. With wearable electronics leading the trend of next generation consumer electronics, designing and fabrication of flexible, inexpensive, lightweight, and high-performance energy storage devices would be the future for energy storage systems. This dissertation starts with a short introduction of energy storage systems, followed by literature reviews on lithium ion batteries and supercapacitors. Then, from chapter 4 to 6, the carbon-based nanocomposite synthesized would be discussed. In Chapter 4, the synthesis of interwoven network of MnO2 nanowires and multi-walled carbon nanotubes (MWCNTs) is described. Working as the lithium ion battery anode materieal, this nanocomposite reveals superior performance by synergistically integrating the two composite materials. Also, with the MWCNT network bendability and strength, a bendable full battery is constructed and examined. Chapter 5 discusses the synthesis of core-shell-structured metal-nitride nanowires with a 3D carbon substrate and its performance for supercapacitor. The electrode exhibits excellent volumetric capacitance and good cycling life stability, attributed to the synergistic integration of vanadium nitride and titanium nitride, as well as the microporous 3D carbon substrate. Chapter 6 describe the doping of conducting polymer (polypyrrole) with graphene quantum dots via electro polymerization. The feasibility of enhancing the capacitive performance of electropolymerized PPy by doping with GQDs is examined. Last but not least, in chapter 7, a general conclusion for all chapters and recommendation for future research work is provided.